Study of scrap tires pyrolysis – Products distribution and mechanism. (15th December 2020) - Li, Dan; Lei, Shijun; Lin, Fawei; Zhong, Lei; Ma, Wenchao; Chen, Guanyi
Abstract：: Pyrolysis process is one of the potential technologies to convert scrap tires (STs) into high-value resources. Though many studies have been conducted, understanding of products characteristics and pyrolysis mechanism is still far from satisfactory to its application. This paper aims to give an in-depth view of STs pyrolysis, providing a uniform products distribution pattern, a fundamental comprehension of the mechanism. Herein, TG – FTIR/MS and Py – GC – TOF/MS were used to investigate the STs pyrolysis, thermal cracking features and pyrolysis paths. The process of STs decomposition contained three interacted parts, with four kinds of products in total, including gaseous, aliphatic hydrocarbons, aromatic hydrocarbons and some other kinds of compounds. Among aromatic hydrocarbons, ethylbenzene, paraxylenes, and mesitylenes were the components with higher content. d -limonene was the dominant composition of aliphatic hydrocarbons. Alkenes and cycloalkenes were initially formed during the pyrolysis process. Then, hydrogenation, substitution and cyclization reactions occurred afterwards. Finally, benzene, benzene derivatives and condensed benzene were generated after complex free radical reaction process. The research provides further insight into the products characteristics and mechanism of STs pyrolysis, which gives a theoretical basis for pyrolysis application of STs and other polymers mixture into high-value products. Highlights: Scrap tires pyrolysis process consists of three interacted parts of diverse rubbers. Scrap tires pyrolysis products mainly concentrate in aromatic hydrocarbons. Contents of aliphatic, aromatic hydrocarbons vary with temperature and reaction time. Principle of scrap tires pyrolysis is dominated by free radical reaction mechanism.